1995
DOI: 10.1159/000173914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyburide on Renal Tubule Transport and Potassium-Channel Activity

Abstract: Renal clearance, microperfusion and patch-clamp techniques were used to investigate the effects of the K-channel blocker glyburide on electrolyte excretion, the transport properties of the thick ascending limb (TAL) of Henle and K-channel activity in the apical membrane of the TAL and of the cortical collecting tubule. Our data suggest that the K-channel blocker glyburide can inhibit transport of Na and K in the TAL by blocking K recycling across the apical membrane. Additionally, inhibition of K secretion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 18 publications
3
53
1
Order By: Relevance
“…Mg-ATP concentrations of ≥1 mM and micromolar concentrations of the sulfonylurea glibenclamide inhibit the 30 pS K channels in the TAL and CCD (19). In vitro studies have suggested that CFTR may be required for inhibition of ROMK by cytosolic ATP (20) and glibenclamide (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Mg-ATP concentrations of ≥1 mM and micromolar concentrations of the sulfonylurea glibenclamide inhibit the 30 pS K channels in the TAL and CCD (19). In vitro studies have suggested that CFTR may be required for inhibition of ROMK by cytosolic ATP (20) and glibenclamide (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Glibenclamide inhibited the transport of Na + and K + in the ascending thick limb of Henle's loop by blocking K + recycling across the apical membrane. 21 This inhibition led to the delivery of the large amounts of fluid and Na + at the initial and cortical collecting tubule. 31 This action was similar to a loop diuretic such as furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that glibenclamide inhibited the transporter of Na + and K + in the ascending thick limb of Henle's loop by blocking K + recycling across the apical membrane. 21 In addition, inhibition of K + secretion in the collecting tubules occurred by decreasing the activity of apical K + channels preventing kaliuresis. 21 A kidneyselective ATP-sensitive potassium channel blocker, U18177 and its 1-adamantyl analog (U37883A) were developed as diuretics and as more selective blockers of the kidney ATP-sensitive channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reminiscent of K ATP channels in excitable tissues, which are heteromultimeric proteins complexes comprised regulatory sulfonylurea receptor (SUR) 1 ATP-binding cassette gene products and pore-forming inward rectifier, Kir 6 subunits (12,13), present evidence from molecular reconstitution studies indicates that ROMK channels also require a ATP-binding cassette protein cofactor to manifest native channel properties. We and others found that coexpression of CFTR with ROMK in Xenopus oocytes leads to the formation of weakly inward rectifying channels that have acquired sensitivity to sulfonylurea agents (14) and ATP-dependent gating properties (15) like the native channel (16,17). With observations that the expression patterns of ROMK (2)(3)(4) and CFTR (18) overlap along the thick ascending limb and collecting duct apical membrane, it seems plausible that the native ROMK secretory channel may be regulated by CFTR in the kidney.…”
mentioning
confidence: 99%